Spinal Anesthesia in Patient with Congestive Heart Failure due to Congenital Atrial Septal Defect, and Pulmonary Hypertension Undergoing Cesarean Section Procedure: A Case Report - Anugerah Ade Periambudi; Rizal Zainal; Mayang Indah Lestari (HM Publisher, 2020)
Introduction. In patients suffering from heart disease, pregnancy is a risk factor for mortality. Heart disease in pregnant women can be in form of rheumatic heart disease, cardiomyopathy, or congenital heart disease. This case report is about the successful spinal anesthesia technique in cesarean section (C-section) patients with congestive heart failure due to congenital atrial septal defect, and pulmonary hypertension (PH). Case presentation. A pregnant woman, 24 years old, planned to have an emergency C-section. She complained about shortness of breath for 2 days before admission. Three months ago, the patient started to feel shortness of breath during activity and also complained her legs swelled. She has a history of congenital heart i.e. atrial septal defect (ASD), but not routinely been treated. Her examination showed tachypnea, murmur, bibasilar fine crackles lung sound, and pretibial pitting edema. Echocardiography showed ASD with pulmonary hypertension. Spinal Anesthesia using 0.5% isobaric bupivacaine 7.5 mg and fentanyl 25 µcg was given before surgery. Drugs was injected in L3-L4 level with the upper target was as high as T6. the head position is raised 30 degrees. Procedure went well and the APGAR score was 8/9, Patient was admitted to the ICU for one day and discharged from hospital at the 5 days of hospital care. Conclusion. Spinal single-shot spinal anesthesia with small doses of bupivacaine and adjuvant can be used as an alternative technique in emergency C-section for patients with congestive heart failure due to congenital atrial septal defect, and pulmonary hypertension.